Desempenho agronômico e qualitativo de cultivares de cebola sob sistema adensado em função da adubação nitrogenada e potássica - Gonçalves, Francisco das Chagas (2018)
The onion is a vegetable of great economic expression, being the third one in economic value in Brazil. Among the nutrients absorbed and exported to the onion bulbs, we highlight potassium and nitrogen. However, the amounts of these nutrients may vary according to the population density and cultivar, directly influencing the productivity and quality of the harvested bulb. Thus, the objective of this work was to evaluate the agronomic and qualitative performance of onion cultivars under a densified system as a function of nitrogen and potassium fertilization. The research consisted of two experiments developed in the years 2015 and 2016, in an ultisol of the Experimental Station of UFERSA, municipality of Mossoró-RN. The experimental design was a randomized block design with four replicates, and the treatments were arranged in a factorial scheme. In 2015, two cultivars (IPA 11 and Rio das Antas) were used with seven doses of potassium (0, 70, 140, 210, 280, 350 and 420 kg ha-1), while the same cultivars were used the following year, but with seven nitrogen doses (0, 45, 90, 135, 180, 225 and 270 kg ha-1). Potassium doses that allowed maximum total and commercial yields were 215 and 216 kg ha-1 of K2O, respectively. Potassium fertilization did not influence the soluble solids neither the percentage of bulbs of classes 2, 3 and 4. There was a reduction in the rate of non-commercial bulbs with the increase of potassium doses. The maximum economic efficiency dose was 211 kg ha-1 of K2O, responsible for a commercial yield of 61.8 t ha-1. Nitrogen increased the nitrogen, chlorophyll a, b and total contents in the leaves, the percentage of bulbs classified as 3 and 4, reducing, however, the percentages of bulbs classified as 2 and non-commercial bulbs. The doses of 108 and 82 kg ha-1 of N provided the highest rates of return for IPA 11 (2.07) and Rio das Antas (2.41), respectively